Justification of the use of forest waste in the power industry as one of the components OF BIO-coal-water suspension fuel. (15th January 2022) - Kuznetsov, G.V.; Malyshev, D. Yu; Syrodoy, S.V.; Gutareva, N. Yu; Purin, M.V.; Kostoreva, Zh. A.
Abstract: The results of the theoretical and experimental studies of the ignition processes of a new class of fuel: bio-water-coal (Bio-WCF) have been presented. The latter has been a water-coal suspension with the addition of 10% leaf or coniferous litter of various tree species, as well as charcoal. It has been established that the addition of biomass to the structure of a water-coal suspension leads to a decrease in the ignition delay time (tign) by 30% under conditions of relatively low oxidizing temperatures. It has been established that when drops of fuel are heated with the addition of charcoal before ignition, dispersion occurs. A mathematical model of the process of ignition of a complex structured bio-water-coal suspension has been developed. According to the results of a numerical simulation, the ignition delay times have been established. A comparative analysis of the theoretical and experimental values of tign has shown their good agreement. Based on the results of the experimental and theoretical studies, the possibility of a significant reduction in the ignition delay time of water-coal suspensions with the introduction of biomass in their structure has been substantiated. Highlights: Ignition of coal/water-biomass fuel particles has been studied. It is shown that forest fuel material significantly accelerates ignition. A detailed mathematical model of the ignition process has been developed. Comparison of theoretical and experimental results showed good agreement.